Local management of trees and woodland resources in Zimbabwe: a tenurial niche approach - Fortmann, L; Nihra, C (Oxford Forestry Institute, University of Oxford, 1992)
This study of forest and woodland management in the rural Zimbabwe begins from two relatively new conceptual starting points: the social forest and the tenurial niche. The social forest is a concept encompassing the more traditional view of forests, taking into consideration all trees used by local people regardless of their location, density, species or size. The tenurial niche takes a more fine grained look at property relations, allowing for the consideration of the complexities that tree tenure introduces to tenure in general. Using key informant interviews, a literature review and rapid rural appraisal, this study examines the prevelance of four management mechanisms (sacred controls, pragmatic controls, the civil contract and new institutions and rules) across various tenurial niches and suggests strategies for improving management and reducing conflict in each niche.